PENGARUH LITERASI KEUANGAN, LINGKUNGAN SOSIAL DAN GAYA HIDUP KONSUMTIF TERHADAP PENGELOLAAN KEUANGAN MASYARAKAT DUSUN BATU ALANG - Ade Kusumawati Umar; Jayanti Mandasari (Publika Citra Media, 2026)
The purpose of this study was to examine the influence of financial literacy, social environment, and a consumer lifestyle on community financial management in Batu Alang Hamlet. The data used were primary data in the form of questionnaires. The sample size was calculated using the Lemeshow formula, resulting in 100 respondents. The sampling technique used was purposive sampling, and questionnaires were distributed directly to respondents. The results showed that financial literacy, social environment, and a consumer lifestyle significantly influenced financial management.